2002
DOI: 10.1016/s0736-0266(02)00004-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth rate does not depend on mantle thickness: an idealized cemented stem construct under torsional loading

Abstract: Retrieval studies indicate that cemented stem loosening in femoral components of total hip replacement can initiate at the stemcement interface. The etiology of the crack propagation process from the stem-cement interface is not well understood, but cracks are typically associated with thin cement mantles. In this study, a combination of experimental and computational methods was used to investigate the fatigue crack propagation process fi-om the stern-PMMA cement interface using a novel torsional loading mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…8 This may result in fracture caused by stem perforation during insertion or premature implant loosening. 17 Crack propagation resulting from cyclic loading occurs at the same rate for any cement thickness, 10 which would result in premature failure of the cement mantle at the thinnest areas.…”
Section: Discussionmentioning
confidence: 99%
“…8 This may result in fracture caused by stem perforation during insertion or premature implant loosening. 17 Crack propagation resulting from cyclic loading occurs at the same rate for any cement thickness, 10 which would result in premature failure of the cement mantle at the thinnest areas.…”
Section: Discussionmentioning
confidence: 99%
“…117 Mechanical and finiteelement studies of the propagation of fatigue cracks in the cement showed that the rate of growth of the crack was independent of the thickness of the cement mantle. 114,118 However, cracks in thin cement reached full-thickness in fewer loading cycles. 118 After loading of cemented stems, regions of thin cement (< 2 mm) presented fewer cement cracks but more full-thickness cracks than the other regions.…”
Section: Stem Philosophiesmentioning
confidence: 99%
“…This has widely been implemented in FEA-models in which the stem-cement interface was invoked as a frictional contact layer (Perez et al, 2009; Hertzler et al, 2002; Verdonschot and Huiskes, 1997). Recently, however, experiments have demonstrated that the movements at the cement-bone interface are also substantial (Mann et al, 2010; Race et al, 2010).…”
Section: Introductionmentioning
confidence: 99%